Use of virtual reality in children in a broad range of medical settings: a systematic narrative review of recent meta-analyses - Emily Antonovics; Grammatina Boitsios; Thomas Saliba (The Korean Pediatric Society, 2024)
Virtual reality (VR) is an emerging method that can be used in many scenarios involving children. VR has been increasingly studied as it has become cheaper, more widely available, and of better quality. In this review of current meta-analyses on the use of VR in children in the medical setting, we examined its role in 5 broad settings where it is used to alleviate pain and anxiety as well as in therapeutic scenarios. The study scope was purposefully broad to highlight a wide range of cases. We searched the ScienceDirect, SpringerLink, Cochrane Library, PubMed, and PMC databases for meta-analyses using VR in pediatric populations in medical settings. The National Institutes of Health quality assessment tool and Quality of Reporting of Meta-analyses statement checklist were used to verify study quality. Six hundred fifty-three articles were retrieved; after the application of the inclusion and exclusion criteria, 11 remained. These meta-analyses included cerebral palsy (4 meta-analyses), attention deficit/hyperactivity disorder (2 meta-analyses), burn care (1 meta-analysis), preoperative anxiety (2 meta-analyses), and needle-involving procedures (2 meta-analyses). The meta-analyses showed broadly positive results, with VR being useful in the areas in which it was applied. This study had several limitations. The meta-analyses consistently highlighted a high level of heterogeneity, making it challenging to draw clear conclusions. Most meta-analyses across all fields yielded encouraging results. However, further studies are required to confirm these findings. Guidelines must be established for future experiments to provide a standard and uniform procedure for reducing the heterogeneity of experimental methods.